Physical activity and motor fitness of children and adolescents - Approaches for serious games - Boes, K.; Krell, J. (International Journal of Computer Science in Sport, 2010)
Physical activity is of inestimable value for health and the motoric development of young people. But in the course of late childhood and adolescence, it becomes less important compared to other leisure activities which do not contain any physical strain. The decrease of physical activity and the resulting decline of motor fitness are reflected in the outcomes of various studies. Hence, strategies are needed to maintain the children`s motivation in physical activity. The enormous popularity of Serious Games could possibly be one strategy because Exergames give an access to sport or to a more active lifestyle. As an isolated movement pattern, Serious Games are no alternative or even a surrogate for real physical exercise. It is difficult to enable a realistically social interaction during virtual sport which has a positive influence on social development. Furthermore indoor video gaming is not comparable to outdoor exercises due to the lack of external influences like wind or audience, which are important contributions to the "adventure" of sport. But in combination and addition to real sport, Serious Games can contribute to the preservation and increase of motor fitness and children`s pleasure in motion.